Testing the Feldstein-Horioka Puzzle in Transition Economies - Adıgüzel, Uğur; Bayat, Tayfur; Kayhan, Selim (Asian Journal of Economic Modelling, 2017)
The relationship between domestic savings and investments has become one of the most important issues discussed in economic theory with globalization of national financial markets. Is really domestic investment financed by global funds or domestic savings are still an important fund source for domestic investments? In this study, the relationship between savings and investments between years 1995 and 2014 is tested by panel data method in the transition economies (Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia, Slovenia, Romania, Bulgaria) transited from the central planning to the free market economy. As a result of the empirical analysis, Feldstein-Horioka puzzle is not valid for most of the transition economies thanks to financial funds came from European Union’s development funds.